From printing to Scielo and Pubmed Central (Colombia Medica, 2014)
The first issue of Philosophical Transactions from the Royal Society published in 1665 is widely regarded as the beginning of modern academic communication through journal articles. This form of presentation was an alternative to books for facilitating the exchange of ideas among scholarly circles. Soon journal collections and scientific libraries were created and eventually an evaluation of the quality of research activity was sought through noting the impact of their publications1. With guidance from the National University of Colombia and support from Scielo Brazil, in 2013 the standards of the US-NLM were implemented and technical endorsement by Pubmed Central was attained.  Colombia Médica´s retention over time is guaranteed by the US-NLM; as of 2014 it will become part of PubMed Central, the free digital archive of biomedical and biological sciences of the U.S. National Institute of Health, which is considered to be the most important digital library in the world. The guidance of the journals by multidisciplinary teams, the policy of free access to its contents, and the technological transfer with the use of free software will help the journals of middle and low-income countries to overcome barriers to diffusion and to maintain technological independence from commercial publishers. Colombia Médica makes an impassioned plea to WHO/PAHO to support BIREME, Brazil and convert SciELO into a certified digital repository.